Life is a tapestry woven with threads of madness": ideology and commitment in Los últimos días de Emmanuel Kant contados por Ernesto Teodoro Amadeo Hoffmann, by Alfonso Sastre - Moyano Arellano, Claudio (Talía. Revista de estudios teatrales, 2023)
This article analyses Los últimos días de Emmanuel Kant contados por Ernesto Teodoro Amadeo Hoffmann, a play with which Alfonso Sastre won the Premio Ciudad de Segovia in 1989. Firstly, the evolution of Sastre's vision of his theatrical practice is studied, with a brief examination of the polemic on possibilism, and an analysis is made of whether this latest theatre can be considered, like the previous stages, political. Secondly, the study of the play focuses not only on the analysis of its sinister and metafictional components, but also on the construction of the last Kant as a theatrical character, and how the abandonment suffered by the German philosopher serves Sastre to denounce the neglect suffered by many elderly people today. This analysis is based on a semiological methodology that is expanded with the study of the play in which Thomas de Quincey describes Kant's last days and with the reflections that Simone de Beauvoir develops about the elderly following the death of her mother.
Keywords: Los últimos días de Emmanuel Kant contados por Ernesto Teodoro Amadeo Hoffmann; Alfonso Sastre; Spanish Contemporary Theatre; Ageism